Marketing communication model for social networks - Klepek, Martin; Starzyczná, Halina (Journal of Business Economics and Management, 2018)
The advent of social media offers yet another set of communication channels which can brand add to integrated marketing communication strategies. Contrary to online advertising available on social media where traditional advertising logic provides an adequate explanation, the content creation and dialogue on social networks still lack sufficient understanding. Consequently, there are many companies which tend to misunderstand customers communication needs within the social media landscape. The obvious reason is the lack of knowledge combined with resistance to change. To bridge this gap, there is a need for empirical research which will clarify the current communication needs of customers. To explore this phenomenon, exploratory research employing questionnaire involving 481 respondents was evaluated with factor analysis method. Identification of three factors provided deeper insights into the understanding of attitudes and behaviour of the current internet population in the Czech Republic. Social network Facebook was chosen as the most widespread not only locally but also globally. Based on this research and previous research studies on communication, a new communication model is proposed in which the element of interaction is the most important. The proposed scheme bears some novel aspects. Firstly, the content in our model is not created outside as in previous models. A social network itself provides a platform for content creation. Secondly, we expanded the physical technical environment of the social network by the abstract brand community in which not only customers but the employees form a vital part. Lastly, the data plays an important role as a valuable tool for feedback and further analysis. Data flow from customer to company enables managers to execute true mass individualisation.